Financial Management and Policy - Horne, James C. Van (Prentice Hall, 2012)
Highly respected for its effective integration of financial theory and practice, this classic book explores the rapidly evolving and exciting theory of finance as it relates to a corporation's investment in assets, financing, and dividends, explains the ways in which analytical techniques are brought to bear on financial decision making, and supplies the institutional material necessary for a solid understanding of the environment in which financial decisions are made. New cases are added, highlighting for readers major issues in financial analysis, valuation, and financing. Extensively revised coverage of relevant topics throughout provides new and updated information on topics such as efficient markets, share repurchase, empirical evidence, electronic funds transfers, loan pricing, private placements, tax treatment of preferred-stock dividends and tax-deductible preferred stock, exotic securities used in corporate finance, and many others. Financial analysis and analytical techniques are discussed in conjunction, applying these topics as they relate to financial decision making with an emphasis on formulating alternatives, analyzing them, and reaching a decision. An excellent resource for professionals in positions such as treasurer, controller, banker, investment banker, investment manager, or chief financial officer.